PRODUCTION PLANNING - Bansal, Shivam; Vashiath, Yogesh; Batra, Ujjwal (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Production planning is he planning of production and manufacturing processes in a company or industry. It utilizes theresource allocation of activities of employees, materials and production capacity, in order to serve different customers. Different types of production methods, such as single item manufacturing, batch production, mass production,continuous production etc. have their own type of production planning. Production planning can be combined with production control into production planning and control, or it can be combined and or integrated into enterprise resource planning. Production planning is used in companies in several different industries, including agriculture, industry, amusement industry, etc. The administrative process that takes place within a manufacturing business and which involves making sure that sufficient raw materials, staff and other necessary items are procured and ready to create finished products according to the schedule specified. A typical large manufacturing business engaging in production planning will aim to maximize profitability while maintaining a satisfied consumer base.